Structure and maintenance of long-term preparation of jumpers in length and triple - Sovenko S. P.; Kolot A. V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Bases of perfection of long-term preparation of jumpers are presented in length and triple by determination of optimum volume of competition practice and training facilities. The results of analysis of long-term dynamics of sporting results of 84 leading athletes-jumpers of the world, which came forward at the greatest level during 10-20 years, are lighted up. Information is systematized more than 50 literary sources, touching structure and maintenance of long-term preparation of athletes-jumpers. Basic priorities of construction of training process of jumpers are set in length and triple on every stage of long-term perfection. The dynamics of volume of competition practice and trainings facilities of jumpers is certain in length and triple in the process of long-term preparation. As a result of experiment information is complemented to scientifically-methodical literatures, touching the training process of jumpers in length and triple on the stage of maintainance of higher sporting trade.